Perspectives and limitations of the Dutch minerals accounting system (MINAS) - Hanegraaf, Marjoleine C.; den Boer, Dirk Jan (European journal of agronomy, 2003)
Nitrogen balance sheets are in widespread use in the Netherlands. First introduced in the 1980s as a voluntary management instrument for dairy farmers, the method has since been developed and formalised in the MINerals Accounting System (MINAS) policy instrument. This is designed to reduce nitrogen (N) and phosphorus (P) losses. As from 2003, MINAS allows a maximum N surplus on grassland of 180 kg N ha −1 on clay/peat soils and 140 kg N ha −1 on dry sandy soils. In 1997, the mean N surplus on dairy farms in the Netherlands was 324 kg N ha −1. Meeting the MINAS loss standards for 2003 was the objective for the farmers participating in the Cows&Opportunities project. Each farm received a tailor-made fertilisation scheme to reduce N losses and optimise N use. Most farms succeeded in realising a lower N loss than planned in their fertilisation schemes. On the experimental dairy farm De Marke the aim is to get the nitrate content in the shallow groundwater below the EU standard of 50 mg l −1 (=11, 3 mg N l −1). Since 1993 the farm has succeeded in realising low N surpluses (1997: 76 kg N ha −1) and low nitrate concentrations (1993–1999 mean: 55 mg l −1). A clear relation was found between N management, as expressed by the N surplus, and nitrate concentration in the groundwater. However, in some years this relation was disturbed. The results show the value of N balance sheets for reducing N losses. From an agricultural point of view, a major advantage of a system such as MINAS is the autonomy it gives farmers to determine how and where they will reduce the N surplus. Using MINAS, however, is no guarantee that a nitrate concentration of 50 mg l −1 will always be achieved.